(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
It is essential to understand the principles of construction and distinctive features of the architectural landmarks of Central Asia and to effectively utilize this knowledge in the present. Professionals in the field should possess the ability to establish the time period of historical architectural monuments. This article explores the architectural landscape of Central Asia during the 13th-14th centuries, shedding light on the emergence of the Khorezm and Bukhara architectural schools, as well as the evolution of urban planning and building architecture during that time.